A infância resiste à pré-escola? - Macêdo, Lenilda Cordeiro de (2014)
Our objectives consisted in understanding what the role of school practices and experiences is in the constitution of the child being and childhood; as well as analyzing how children live their childhood condition in the institution of early childhood education and how they reproduce and produce culture in the school environment. The starting point to develop this research was the following thesis: the design of early childhood education as children socialization has been hegemonic; therefore, very early he/she needs to become a student, be formed / shaped by the grammar school. However, children as individuals produced in and through culture act, transgress the rules and construct own meanings and own cultures inside the school environment, intervening in this specific context and in the social reality as a whole. To develop this research we chose the interpretive epistemological paradigm, conducting a research with characteristics of a case study, inspired by the ethnographic method. The techniques of systematic observation, document analysis and informal interviews were used in order to produce the used data. The participant observation happened in an early childhood institution in Campina Grande - PB, which attends children from 2 to 5 years old in the nursery (maternal) and in preschool stages. The observation period was from July 2011 to May 2012 totalizing 57 days and 160 hours of observations, and in order to record data, it were used field journal, camera and video. Twenty eight (28) children from two classes of preschool stage and 4 teachers participated directly in the research. In general, the research results indicated a pedagogical practice with explicit goals of preparation / literacy, leaving aside and / or naturalizing other key languages to the child, such as playing, drawing and painting, animated cartoon, musicality, body expression and fantasy. It was also found other less explicit curricular practice, called pedagogy of control, which aims to control/limit children orality, thought, body, desires, imagination, creativity and fantasies. This implicit, but tangible practice, places children exactly in the place which was historically and culturally established for them: the underage, subalternity, domination, subservience. The collected data also indicated a perspective of school work permeated by extensive reading and writing activities thereby shortening children s free time and revealed some of the nuances of children's peer relationships: such as friendship, fragility and inequality in peer relationships, which in general reproduce the adult values and criteria. However, despite the pedagogy of control, children build cultures during the class activities schedule (free and directed), at the park, through games and diverse actions. Finally, our data indicate a clear children willingness in resisting the pedagogy of control, this is because they, as individuals who monitor their own actions, at the same time they are coerced by the institutional structure to assume the passive and subservient student identity, they create strategies to resist the preschool shape / frame , in other words , the structure. Regarding what was said above, we conclude that there is no place for childhood in the searched preschool. The pedagogy of control does not provide childhood experience; however, children while social agents, act to contrast the grammar school, they resist this curriculum, these practices and they are able, ad hoc basis, to reproduce and produce childhood cultures modifying the current structure. In summary, children live / assume their status of childhood in preschool. It is confirmed, in this sense, our initial thesis.